2002
DOI: 10.1897/1551-5028(2002)021<0848:citpqy>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Potential Quantum Yield of Photosystem Ii and the Integrity of Cell Membranes Relative to the Elemental Content of the Epilithic Desert Lichen Ramalina Maciformis

Abstract: Abstract-The present study used the epilithic fruticose lichen Ramalina maciformis to investigate the occurrence of mineral elements, including heavy metals, at a distance of up to 50 km from the industrial region in Ramat Hovav in the Negev Desert, Israel. The major objective of this study was an analytical comparison of elemental content and physiological parameters of lichen vitality, apart from a test of the applicability of this specific lichen in investigations of air pollution. The Ca, Cr, Cu, K, Mg, Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 72 publications
2
3
0
Order By: Relevance
“…The significant positive correlations between the concentrations of the main heavyelement contaminants in the study area (Cr, Pb, Sb and Zn) and the values of electrical conductivity in exposed lichens confirmed the hypothesis above. This is consistent with the results of other studies that found higher values of electrical conductivity in lichen transplants affected by heavy element accumulation (Adamo et al, 2003;Garty et al, 2002;Garty et al, 1998b). Paoli and Loppi (2008) also observed that cell membrane damage in E. prunastri lichens was correlated with air quality.…”
Section: Table 3 4 Discussionsupporting
confidence: 93%
“…The significant positive correlations between the concentrations of the main heavyelement contaminants in the study area (Cr, Pb, Sb and Zn) and the values of electrical conductivity in exposed lichens confirmed the hypothesis above. This is consistent with the results of other studies that found higher values of electrical conductivity in lichen transplants affected by heavy element accumulation (Adamo et al, 2003;Garty et al, 2002;Garty et al, 1998b). Paoli and Loppi (2008) also observed that cell membrane damage in E. prunastri lichens was correlated with air quality.…”
Section: Table 3 4 Discussionsupporting
confidence: 93%
“…This is consistent with the results of other studies that found higher values of electrical conductivity in lichen transplants affected by heavy element accumulation (Adamo et al, 2003;Garty et al, 2002;1998b). Paoli and Loppi (2008) also observed that cell membrane damage in E. prunastri lichens was correlated with air quality.…”
Section: Discussionsupporting
confidence: 93%
“…The study showed a relation between NDVI decrease and heavy metal-induced loss of photosystem (PS) II functioning expressed as a variable to maximum fluorescence ratio (F v /F m ) decrease. The F v /F m ratio decrease is caused mainly by a partial disintegration of PS II (Garty et al 2002).…”
Section: Introductionmentioning
confidence: 96%